THE EFFECT OF GLYCOLIC ACID AND VITAMIN C TOPICAL IN FRECKLES EFFICACY - Tiffani Sandradewi Wignjosoesastro; Widyawati Widyawati; Rahmat Sugianto (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Abstract Background: Freckles are small dark-spot hyperpigmentation on the face, upper body, and back of the hands. This hyperpigmentation develops as a result of melanocyte activity by the combination of genetic predisposition located on the basal layer and sun exposure. Glycolic acid and vitamin C are widely used as a depigmentation agent. The component of vitamin C is unstable, hence, it is often used more effective when it binds to other depigmentation agents, such as glycolic acid to develop better depigmentationObjective: The aim of this study was to prove the efficacy of combination of glycolic acid and vitamin C in freckles.Methods: True experimental study with one group pre and post-test group design. Fifteen freckles patients with inclusion and exclusion criteria received combination therapy of glycolic acid and vitamin C topical for 30 days. Clinical evaluation using Freckles Refinement Score and photography was recorded before and after therapy. The statistical analyses used was Wilcoxon test.Results: There was a significant value (p = 0.000) for improvement of the Freckles Refinement Score after received the combination of glycolic acid and vitamin C topical.Conclusion: The combination of glycolic acid and vitamin C was effective for Freckles.